INFORMATION TECHNOLOGY SERVICES SUPPORT FOR EMERGENCIES - Spicer, Donald Z. (Online Learning, 2008)
For at least the last quarter century, enterprises—including higher education institutions—have increasingly relied on Information Technology Services (ITS) for business functions. As a result, IT organizations have had to develop the discipline of production operations as well as recovery procedures to respond when those operations are disrupted. More recently, both the academic and research mission activities of higher education institutions have become increasingly supported by ITS. That ITS touches almost every activity of a higher education institution puts special emphasis on IT services in emergency situations. This paper outlines an evolution of thinking regarding the role of ITS in enterprise emergency response.